ANALISA PENGARUH MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK SEKOLAH DASAR - Christiana Switaningsih; Ngatmini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Many elementary school students in grades I and II are not fluent in reading simple texts, have difficulty distinguishing letter shapes and have difficulty reading consonants. This study aims to see how far the influence of image media to improve early reading skills in elementary school children using the literature review method. This literature study was conducted by analyzing several research articles from 2019 to 2023. Data is obtained from Google Schoolar with keywords image media, reading beginning, elementary school. The results of this literature obtained five articles that fit the inclusion and exclusion criteria. The results of this literature study show an increase in the initial reading ability of elementary school students using image media. This is evidenced by analyzing eight articles that show an average percentage increase in results. Thus, the use of image media is very helpful for students in improving their initial reading skills in elementary school.